1998
DOI: 10.1007/s002280050441
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian pharmacokinetic estimation of vinorelbine in non-small-cell lung cancer patients

Abstract: We demonstrated that Bayesian estimation allows, at minimal cost and minimal disturbance for the patient, the determination of several vinorelbine pharmacokinetic parameters and therefore dose adaptation from as few as two drug concentrations, measured at 6 h and 24 h after infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
4
7
0
Order By: Relevance
“…The PK of pemetrexed and vinorelbine were consistent with data obtained with single-agent chemotherapy (Marquet et al, 1992;Leveque and Jehl, 1996;Sabot et al, 1998). There was no evidence for PK interaction between the two drugs.…”
Section: Discussionsupporting
confidence: 79%
“…The PK of pemetrexed and vinorelbine were consistent with data obtained with single-agent chemotherapy (Marquet et al, 1992;Leveque and Jehl, 1996;Sabot et al, 1998). There was no evidence for PK interaction between the two drugs.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, systemic exposure was lower at a given dose compared with that reported in previous adult studies but was proportionate to clearance. The calculated area under the plasma concentration-time curve in this study at 30 mg/m 2 was 676 ng/mL-h compared with 800 to 900 ng/mL-h reported in adult patients (19,20). Thus, we believe that a weekly schedule of i.v.…”
Section: Discussionmentioning
confidence: 39%
“…No previous report has defined, on a large number of patients, the extent to which demographic variables or other covariates could influence the disposition of vinorelbine. Only two analyses have been performed and on a small number of patients ( n ≤12) to either establish a limited sampling strategy [27] or to examine the effect of age on vinorelbine pharmacokinetics [28]. Such approaches did not yield a relevant population model because of the relatively high interpatient variability on clearance and volume of distribution.…”
Section: Discussionmentioning
confidence: 99%